STRATEGI KOMUNIKASI RISIKO KEMENTERIAN KESEHATAN REPUBLIK INDONESIA DALAM UPAYA PENANGGULANGAN COVID-19 MELALUI MEDIA SOSIAL - Sri Devi Octavia Surbakti; Indra Budi Laksana (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2021)
The objective of this study is to analyze the risk communication strategies used by the Ministry of Health of the Republic of Indonesia to control COVID-19 using social media, especially YouTube and Instagram. This study utilized qualitative descriptive research methods. The results indicate that the use of social media to overcome COVID-19 by the Ministry of Health of the Republic of Indonesia has not been conducted effectively because there are still principles and elements of risk communication that have been overlooked.. Thus, it is necessary to assess the performance of the Directorate of Health Promotion and Community Empowerment of the Ministry of Health of the Republic of Indonesia in order to determine which efforts can be optimized to improve risk communication through public engagement, both online and offline, in order to effect changes in community behavior related to preventing and overcoming COVID -19.